Lignocellulosic Biomass Pretreatment for Biorefinery: A Review - Zulfan Adi Putra (Indonesian Journal of Science and Technology, 2018)
Lignocellulosic biomass consists of cellulose, hemicellulose, and lignin, which have the potential to produce the so-called green chemicals. Many processes are available at different scales (e.g. labs, pilots, demos, commercials), utilizing lignocellulosic biomass as the raw material. Due to its complicated chemical structures, lignocellulosic biomass must be pretreated before it can be processed further. Simultaneous separation of cellulose, hemicellulose, and lignin from the biomass is an important step to maximize the full potential of the biomass. In this review, several well-known biomass pretreatment technologies are evaluated. These are low pH process (e.g. dilute acid, steam explosion, hot water liquid, and concentrated acid), high pH (e.g. NaOH, lime, NH3), organosolv, ozonolysis, CO2 explosion, and ionic liquids. The objective of this review is to understand how effective the pretreatment process for separating cellulose, hemicellulose, and lignin. Based on this review, organosolv is the only pretreatment process that is capable of separating cellulose, C5 sugars (from hemicellulose), and lignin, simultaneously. This process is currently at pilot scales of 30 – 100 ton per day of biomass feedstock.